PENERAPAN SANKSI PIDANA PADA PUTUSAN NO. 870/PID.B/2016/PN.JKT.SEL. DITINJAU DARI UNDANG-UNDANG NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DAN UNDANG-UNDANG NO. 2 TAHUN 1981 TENTANG METROLOGI LEGAL (STUDI KASUS PUTUSAN NO. 870/PID.B/2016/PN.JKT.SEL.) - Ardi Ardi; Firman Wijaya (Jurnal Hukum Adigama, 2019)
Gasoline or fuel oil is a necessity for society, especially for motor vehicle owners. In Indonesia, Pertamina as one of the fuel suppliers cooperates with the private sector to offset business competition with gas stations from abroad. In terms of Pertamina gas stations that are partnering with the private sector, cheating is not uncommon, such as the dosage of fuel oil that is not in accordance with the truth. As happened at Pertamina gas station in Rempoa area where the perpetrators involved 3 gas station managers and 2 gas station employees using additional equipment installed in the fuel dispenser and controlled using a remote control. With the existence of criminal sanctions in both laws, Act No. 8 of 1999 concerning Consumer Protection and Act No. 2 of 1981 concerning Legal Metrology, so that the actions of these perpetrators can be criminally accountable as can be seen in the Decision of the South Jakarta District Court Number 870/Pid.B/2016/PN.JKT.SEL. How is the application of criminal sanctions on Decision No. 870/ Pid.B/2016/PN.JKT.SEL. reviewed from Act No. 8 of 1999 concerning Consumer Protection and Act No. 2 of 1981 concerning Legal Metrology? The author use normative legal research and uses interview data as supporting data. The results of the study revealed that the criminal sanctions imposed on the three gas station managers were considered appropriate even though the maximum sentence was not applied, but the judges had their own freedom and legal considerations in deciding cases.